Landscape Genetics in the Neotropics - Silva Carvalho, Carolina da; Côrtes, Marina Corrêa [UNESP] (Springer Nature, 2023)
Landscape genetics is an interdisciplinary field that aims at assessing the influence of environmental and landscape factors on microevolutionary processes, especially gene flow and natural selection. It provides a powerful toolbox that can be applied to understand processes and patterns of biodiversity and establish informed conservation strategies in a spatial context. The Neotropics, home to extraordinary biodiversity, suffer from alarming rates of anthropogenic transformation and, hence, benefit from the landscape genetics framework. Here, we revisit fundamental concepts and provide an overview of common analytical methods. We then present a scientometric analysis of landscape genetic studies in the Neotropics and describe potential applications. Overall, there is ample opportunity for growth in neotropical studies. Based on our search criteria we compiled a total of 65 studies, with an increasing trend in publication over time. Brazil and Mexico are the main contributors to the literature, whereas most of the American tropical countries have not conducted landscape genetic studies. The studies tend to be population-based and focus on landscape features that influence genetic diversity and connectivity. Very few apply genomic tools to investigate local adaptation. Lastly, we discuss some of the challenges and opportunities for future (neo)tropical research.